Variational Setting - Steinmann, Paul (Spatial and Material Forces in Nonlinear Continuum Mechanics, 2022)
This chapter expands on the variational setting in terms of extended Hamilton and Dirichlet principles for conservative elasto-dynamic and elasto-static cases, respectively, and carefully analyzes the resulting spatial and material Euler-Lagrange equations.
CRIS-Team Scopus Importer:2022-04-15